1982
DOI: 10.1159/000457400
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Methicillin, Nafcillin and Oxacillin in Pediatric Patients

Abstract: 68 patients (from newborns to 18 years of age) were studied prospectively for adverse effects associated with methicillin, nafcillin and oxacillin. Hematologic, liver and renal function tests were monitored before and during therapy. 3 of 28 patients receiving methicillin developed eosinophilia within 5-8 days. Of 32 patients on nafcillin, 2 had neutropenia within 4-13 days, 3 had eosinophilia within 1-4 days and 1 elevated liver enzymes on day 3. Of 8 patients receiving oxacillin, 1 developed neutropenia on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1998
1998
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In a larger study of 119 patients treated with the antibiotic, 8.1% of patients developed liver function abnormalities [1]. Nahata and co-workers described transaminitis occurring in one of 32 patients treated with nafcillin [3]. Table 2 lists reported cases of hepatocellular injury induced by various antibiotics and Table 3 [4-7] lists the reported cases of nafcillin-induced hepatocellular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger study of 119 patients treated with the antibiotic, 8.1% of patients developed liver function abnormalities [1]. Nahata and co-workers described transaminitis occurring in one of 32 patients treated with nafcillin [3]. Table 2 lists reported cases of hepatocellular injury induced by various antibiotics and Table 3 [4-7] lists the reported cases of nafcillin-induced hepatocellular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A single-centre prospective study (Nahata 37 ) compared children who received IV methicillin, nafcillin or oxacillin in an inpatient setting and found an incidence of DILI of 0% (0/28), 3.1% (1/32) and 12.5% (1/8), respectively. High IV doses were used with mean doses of 106 mg/kg/day (SD ± 31.2) for methicillin, 118 mg/kg/day (SD ± 33.9) for nafcillin and 153 mg/kg/day (SD ± 24.6) for oxacillin.…”
Section: Resultsmentioning
confidence: 99%
“…Two prospective studies of IV methicillin found an overall incidence of DILI of 14/103 (13.6%). 37 , 39 In both studies, children had LFTs performed weekly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nahata et al. reviewed the ADRs of nafcillin, methicillin and oxacillin in 68 paediatric patients 4 . Elevated liver enzyme, neutropenia and eosinophilia were the major adverse reactions in the oxacillin treatment group.…”
Section: Discussionmentioning
confidence: 99%